2023
DOI: 10.1002/aenm.202301765
|View full text |Cite
|
Sign up to set email alerts
|

Cathode Electrolyte Interface Engineering by Gradient Fluorination for High‐Performance Lithium Rich Cathode

Lu Di,
Chen Yufang,
Sun Weiwei
et al.

Abstract: Despite their ultrahigh specific capacity, lithium‐rich layered oxide cathodes are still plagued by challenges such as poor cycle stability and notorious voltage decay, which are primarily attributed to surface issues such as the release of lattice oxygen and interfacial side reactions. In this study, a facial strategy of gradient fluorination is adopted to construct a thin but robust LiF‐rich cathode electrolyte interface (CEI), highly enhancing the stability of the interface of lithium‐rich oxides. Experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(13 citation statements)
references
References 61 publications
1
12
0
Order By: Relevance
“…The surface of the cathode will generate a CEI film upon initiating the charging and discharging process. When the CEI film is completely generated into a stable interfacial film, the transmission of lithium ions tends to be stabilized, which in turn reduces the charge transfer resistance. …”
Section: Resultsmentioning
confidence: 99%
“…The surface of the cathode will generate a CEI film upon initiating the charging and discharging process. When the CEI film is completely generated into a stable interfacial film, the transmission of lithium ions tends to be stabilized, which in turn reduces the charge transfer resistance. …”
Section: Resultsmentioning
confidence: 99%
“…The peak intensity of LiF derived from LiDFP + BVM dual-additives electrolyte is much stronger than baseline electrolyte. As LiF has been generally considered an ideal interfacial component to enhance Li + transfer kinetics between cathode and electrolyte, the cycling performance of NCM95 cathodes on LiDFP + BVM electrolytes was then improved remarkably, as aforementioned. It has been reported that a certain amount of Li x PO y F z and Li 3 PO 4 deposited on the surface to compose CEI could be beneficial to cathode structural stability and ionic conductivity. , As shown in Figure d of the P 2p spectrum, the characteristic peaks of Li x PO y F z and Li 3 PO 4 located around 134 eV increase rapidly due to the preferential decomposition of the LiDFP + BVM dual additives in comparison with baseline electrolyte, which is in accordance with the interfacial improvement of NCM95 cathodes incorporated into the LiDFP + BVM electrolyte.…”
Section: Resultsmentioning
confidence: 99%
“…The peak intensity of LiF derived from LiDFP + BVM dual-additives electrolyte is much stronger than baseline electrolyte. As LiF has been generally considered an ideal interfacial component to enhance Li + transfer kinetics between cathode and electrolyte, 43 the cycling performance of NCM95 cathodes on LiDFP + BVM electrolytes was then improved remarkably, as aforementioned. It has been reported that a certain amount of Li x PO y F z and Li 3 PO 4 deposited on the surface to compose CEI could be beneficial to cathode structural stability and ionic conductivity.…”
Section: Interfacial Enhancement Mechanism Of Ncm Cathodementioning
confidence: 91%
“…On the one hand, the Ho 2 O 3 coating can reduce the corrosion from the electrolyte on the material, reduce the dissolution of TM, and improve the structural stability of the material. On the other hand, the abundance of oxygen vacancies in the modified material can enhance oxygen binding and reduce oxygen release …”
Section: Results and Discussionmentioning
confidence: 99%